2021
DOI: 10.1007/s12011-021-02573-w
|View full text |Cite
|
Sign up to set email alerts
|

First Insights Into Trace Element Accumulation by Philoscia affinis (Crustacea, Isopoda): a Novel Tracer to Assess Soil Contamination in Lowland Plains?

Abstract: Isopods are terrestrial invertebrates that accumulate trace elements in large quantities, thus providing information on levels of soil contamination. However, the accumulation pattern seems to be species dependent. For this study, specimens of Philoscia affinis (Isopoda, Oniscidea) and soil samples were collected from both a protected area (site 1) and urban roadside (site 2) in the low plain of Friuli-Venezia Giulia (northeast Italy) to determine whether P. affinis could serve as a potential candidate for mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that the level of accumulation in the organism of Isopods correlates with the level of contamination in rural, suburban and urban sites (Papp et al, 2019;Simon et al, 2016), and that the level of accumulation depends on the level present in food and soil (Heikens et al, 2001;Van Straalen et al, 2001). The accumulation pattern appears to be species-dependent (Pastorino et al, 2021):…”
Section: Statistical Analysesmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous studies have shown that the level of accumulation in the organism of Isopods correlates with the level of contamination in rural, suburban and urban sites (Papp et al, 2019;Simon et al, 2016), and that the level of accumulation depends on the level present in food and soil (Heikens et al, 2001;Van Straalen et al, 2001). The accumulation pattern appears to be species-dependent (Pastorino et al, 2021):…”
Section: Statistical Analysesmentioning
confidence: 93%
“…A lot of studies report the high capacity of bioindication of Isopoda, especially their capacity to accumulate contaminants (Dallinger et al, 1992;Pastorino et al, 2021;van Gestel et al, 2018), in fact they are also used as useful bioindicators of environmental contamination by heavy elements, which they uptake and accumulate (Odendaal & Reinecke, 2004a, 2004bPaoletti & Hassall, 1999;Vijver et al, 2006;Witzel, 1998).…”
Section: Bioindication and Hepatopancreasmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have reported the high capacity of bioindication of Isopoda, especially its capacity to accumulate contaminants (Dallinger et al 1992 ; Pastorino et al 2021 ; van Gestel et al 2018 ). They are also used as useful bioindicators of environmental contamination by heavy elements, which they uptake and accumulate (Odendaal and Reinecke 2004a , 2004b ; Paoletti and Hassall 1999 ; Vijver et al 2006 ; Witzel 1998 ).…”
Section: Introductionmentioning
confidence: 99%